Individual subjective well-being during the COVID-19 pandemic - Trinh Quang Long (Asian Development Bank Institute (ADBI), 2021)
This paper examines how contextual and institutional factors are associated with individual subjective well-being, which is measured by individuals' happiness, during the early stage of the COVID-19 pandemic. Using data collected in the People's Republic of China (PRC), the Republic of Korea, Japan, Italy, the United Kingdom (UK), and the four biggest states of the United States (US) in April 2020, we find that the financial effects (represented by employment and income change) and nonfinancial effects (represented by experiencing negative nonfinancial effects including mental health issues and enjoying positive benefits) caused by nonpharmaceutical measures to contain the spread of COVID-19 are associated with individual subjective well-being. Moreover, positive benefits could reduce the likelihood of becoming unhappy for those who have experienced negative nonfinancial effects or those who have lost their jobs. The results also suggest that the degree to which people agree with their government's approach to dealing with the COVID-19 pandemic is positively correlated with their happiness. The risks associated with the pandemic, however, are only slightly associated with people's happiness. We also find that the correlation between the above factors and individual well-being varies from country to country.
Keywords: D0; D60; D62; I12; 330; subjective well-being; happiness; financial effects; mental health effect; COVID-19